Appetitive operant conditioning in mice: heritability and dissociability of training stages - Malkki, Hemi A.; Donga, Laura A.; De Groot, Sabine E.; Battaglia, Francesco P.; Pennartz, Cyriel M. (Frontiers in Behavioral Neuroscience, 2010)
To study the heritability of different training stages of appetitive operant conditioning, we carried out behavioural screening of 5 standard inbred mouse strains, 28 recombinant-inbred (BxD) mouse lines and their progenitor strains C57BL/6J and DBA/2J. We also computed correlations between successive training stages to study whether learning deficits at an advanced stage of operant conditioning may be dissociated from normal performance in preceding phases of training. The training consisted of two phases: an operant nose poking phase, in which mice learned to collect a sucrose pellet from a food magazine by nose poking, and an operant lever press and nose poking phase, in which mice had to execute a sequence of these two actions to collect a food pellet. As a measure of magazine oriented exploration, we also studied the nose poke entries in the food magazine during the intertrial intervals at the beginning of the first session of the nose-poke training phase. We found significantly heritable components in initial magazine checking behaviour, operant nose-poking and lever press-nose poking. Performance levels in these phases were positively correlated, but several individual strains were identified that showed poor lever press-nose poking while performing well in preceding training stages. Quantitative trait loci mapping revealed suggestive likelihood ratio statistic peaks for initial magazine checking behaviour and lever press – nose poking. These findings indicate that consecutive stages towards more complex operant behavior show significant heritable components, as well as dissociability between stages in specific mouse strains. These heritable components may reside in different chromosomal areas.